Non-Destructive Investigation of A 44-Year-Old RC Structure Exposed to Actual Marine Tidal Environments Using Electrochemical Methods - Astuti, Pinta; Kamarulzaman, Khalilah; Hamada, Hidenori (International Journal of Integrated Engineering, 2021)
Investigation of deterioration progress in marine structures without destroying them is crucial as early detection of damage before applying the suitable remedial measures. This study presents a series of non-destructive assessment on a 44-year-old naturally corroded RC structure exposed to marine tidal environments using observation of defective appearances and electrochemical tests. The visual observation was conducted by inspecting the corrosion condition of steel bars, crack patterns, and the spalling of concrete cover. The electrochemical investigations carried out in this research consisted of the half-cell potential mapping, the electrical resistivity of concrete, and the corrosion rate of steel bars. The results revealed that electrochemical test results conducted in this research were in good agreement with the actual deterioration degree checked by defective appearances. The RC structure was categorized as Grade II-1 (first half of the acceleration stage). Based on the deterioration degree, both applications of small direct current to control the potential of steel bars in immunity condition and patch repair method by removing the chloride contaminated concrete were recommended as appropriate repairing strategies, and they could extend the service life the of structure.